The Effect of Drying Temperature of Carica pusbecens Seeds on Secondary Metabolite - Elok Widayanti; Hanandayu Widwiastuti; Rany Adelina; Indah Cahyaning Wulan (Health Notions, 2023)
Papaya mountain (Carica pubescens) is one of the typical plants that grows in the Dieng Plateau. Seeds of mountain papaya (Carica pubescens) are a by-product of candied carica production which has not been widely used. All carica seeds obtained were cleaned of mucilage and then treated with drying temperatures of 30, 40, 50 and 60oC. The purpose of this study was to examine the secondary metabolite content of the ethanol extract of mountain papaya seeds with variations in drying temperature. The type of research used was experimental. Drying temperature was one of the factors that affect the quality of simplicia. The extraction method used maceration with 70% ethanol as a solvent. Maceration was carried out for 3 days followed by a phytochemical screening test. The results of the phytochemical test showed that the ethanol extract of papaya seeds at temperatures of 30, 40, 50 and 60oC contained alkaloids, flavonoids, saponins, tannins and triterpenoids. Keywords : Carica pubescens; temperature variations; maceration